Effect of surface stoichiometry on the non-alloyed ohmic contact to N-face n-GaN. (September 2020) - Zhou, Rui; Feng, Meixin; Wang, Jin; Zhong, Yaozong; Sun, Qian; Liu, Jianxun; Huang, Yingnan; Zhou, Yu; Gao, Hongwei; Ikeda, Masao; Li, Zhiyun; Zhao, Yanfei; et al.
Highlights: This letter reveals the surface stoichiometry of N-face n-GaN has a significant effect on the electrical property of non-alloyed ohmic contact, and can be tuned by plasma treatment. Combining with X-ray photoelectron spectroscopy, we have confirmed that it is indispensable to remove GaOx  layer prior to the metal deposition. More importantly, the contact property depends greatly on the plasma species and the radio frequency power. Finally, a non-alloyed ohmic contact to N-face n-GaN has been successfully achieved. Abstract: This letter reports a systematic study about the effect of surface stoichiometry induced by inductively coupled plasma (ICP) etching on the ohmic contact to N-face n-GaN. It is found that N-face n-GaN surface has a very high activity towards oxygen adsorption. And it is indispensable to remove GaOx layer on the N-face n-GaN surface prior to the metal deposition to realize ohmic contact. Moreover, the radio frequency power of the ICP etching and the plasma species greatly affect the surface stoichiometry and the electrical property of the ohmic contact to N-face n-GaN. X-ray photoelectron spectroscopy was implemented to characterize the surface stoichiometry of N-face n-GaN after plasma treatment and reveal the mechanism behind the phenomena. As a result, a non-alloyed ohmic contact to N-face n-GaN has been successfully achieved in a reproducible way.